(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
In 2012 the European Regional Office of WHO published a new health policy strategy, Health 2020, and an accompanying European Action Plan [1, 2], with both documents since being endorsed by the 53 member states. Following consultation with member states, a series of overarching targets have been established in the three areas of Health 2020: i) reducing the burden of disease and risk factors; ii) enhancing health and well- being; and iii) improving governance and systems for health. The WHO is now working with member state governments to develop ‘Regional’ Health 2020 targets [3, 4]. If Health 2020 is to achieve these goals, the actions that flow from it must be based on the best...